Meningioma: A Clinicopathological Correlation - Shenoy, Asha; Khade, Shalaka; Waghmare, Ramesh (Annals of Pathology and Laboratory Medicine, 2019)
Background: This study aimed at classifying meningioma and its variants based on histology, and study its clinicopathological correlation. This analytical study conducted in a tertiary referral centre included clinical presentation, radiological features and histopathological correlation of meningioma. The grading system of meningioma is based on histological features. Difference in subjective assessment can hamper this grading system. A continuous revision of the histopathology of meningiomas and taking into account precise definitions of features such as small cell changes, hypercellularity, sheeting, necrosis, and mitotic count is necessary to improve the accuracy for diagnosis grading of these tumours. Methods: A retrospective and prospective study of meningiomas was carried out in the department of Pathology at a tertiary care hospital over a period of 5 years (July 2011 to June 2016). Clinical presentation, radiological features and histological findings were taken into consideration. Result: Of the 277 cases of lesions of central nervous system, 63 cases were diagnosed as meningioma, the incidence being 22.74%. Most these cases were in the 4th to 6th decade of life (71.42%). The overall male to female ratio was 1: 2.3. The commonest clinical feature was headache (58.73%) followed by limb weakness (33.33%). The most common location was cerebral hemisphere (49.20%). There were 7 cases of spinal meningioma. Most of the meningiomas were hyperdense (60.8%) on CT and iso to hypointense (90%) on MRI.Most of the cases were Grade I meningiomas (88.89%), meningothelial and transitional being the most common histological subtypes. Two of the grade II meningioma cases showed presence of brain invasion. Conclusion: Histopathological examination is an imperative tool for confirmatory diagnosis due to the diverse histological variants. Also, the prognosis of the disease depends on histopathological grading of the lesion.